Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1128/iai.01348-06
|View full text |Cite
|
Sign up to set email alerts
|

The Human Immunodeficiency Virus Type 1 Tat Protein EnhancesCryptosporidium parvum-Induced Apoptosis in Cholangiocytes via a Fas Ligand-Dependent Mechanism

Abstract: While Cryptosporidium parvum infection of the intestine has been reported in both immunocompetent and immunocompromised individuals, biliary infection is seen primarily in adult AIDS patients and is associated with development of AIDS cholangiopathy. However, the mechanisms of pathogen-induced AIDS cholangiopathy remain unclear. Since we previously demonstrated that the Fas/Fas ligand (FasL) system is involved in paracrine-mediated C. parvum cytopathicity in cholangiocytes, we also tested the potential synergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…In addition, a neutralizing antibody to Fas also showed a significant inhibitory effect on the associated apoptosis (Fig. 6), consistent with our previous results demonstrating that Fas/Fas-ligand pathway is involved in the apoptosis in the co-cultured Jurkat cells [28,33]. Thus, besides the activation of the Fas/Fas-ligand pathway, miR-513-mediated expression of B7-H1 also contributes to the apoptotic cell death in T-cells induced by co-culture with C. parvum -infected cholangiocytes.…”
Section: Resultssupporting
confidence: 91%
“…In addition, a neutralizing antibody to Fas also showed a significant inhibitory effect on the associated apoptosis (Fig. 6), consistent with our previous results demonstrating that Fas/Fas-ligand pathway is involved in the apoptosis in the co-cultured Jurkat cells [28,33]. Thus, besides the activation of the Fas/Fas-ligand pathway, miR-513-mediated expression of B7-H1 also contributes to the apoptotic cell death in T-cells induced by co-culture with C. parvum -infected cholangiocytes.…”
Section: Resultssupporting
confidence: 91%
“…However, C. parvum biliary infection and AIDS cholangiopathy remain significant problems in individuals who lack access to or fail to respond to HAART. We have previously demonstrated that C. parvum is cytopathic to cultured uninfected bystander cholangiocytes through a paracrine Fas/FasL-dependent apoptotic mechanism [25] and that HIV-1 Tat protein sensitizes cultured cholangiocytes to C. parvum –induced Fas/FasL-dependent apoptotic cell death [45]. Thus, Tat not only sensitizes cholangiocytes, a cell type refractive to HIV-1 infection, to the cytopathic effect of biliary cryptosporidiosis, but our present results suggest that Tat also inhibits the response of cholangiocytes to this opportunistic pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested in other tissues, macrophage phagocytosis of apoptotic cells containing the pathogens may contribute to antigen presentation. Apoptotic cell death of cholangiocytes during microbial infection has been reported both in vivo and in vitro 67 , 68 , 69 . However, whether apoptotic cell death of cholangiocytes is involved in the antigen presenting process is unclear.…”
Section: Activation Of Cholangiocyte Immune Responsesmentioning
confidence: 99%